Tourism-Related Gentrification: The Case of Sóller (Mallorca) - Joan Rossello-Geli (Urban Science, 2025)
The research herein presented aims to analyze the impacts of gentrification in a medium-sized Mallorca municipality because of the tourism accommodation changes. Using the available data from national and regional official sources, qualitative research is undertaken. The main findings show how gentrification has exacerbated issues such as rising real estate prices and the loss of houses, which are nowadays devoted to tourist rentals or boutique hotels, thus not available for the local population. Another effect is a displacement of young local residents from Sóller towards other island municipalities and, finally, the presence of conflicts over the use of public spaces. Even if the local authorities already implement some measures, it is concluded that more measures should be included in order to avoid the increase in “tourismphobia” attitudes related to the gentrification process and the public space occupation.